2014
DOI: 10.12816/0010945
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Training and Development on Employee Performance : A Case Study of Escon Consulting

Abstract: The study focuses on the impact of training and development on employee performance at ESCON. Training and development is a critical process, which seeks to improve the performance of workers in the organisation. In order to form competent committees, employees' relevant expertise and intellectual capacity needs to be improved. Some of the projects executed by ESCON fail at an embryonic stage owing to the fact that tenders are awarded to the lowest priced contractor. Moreover, the ineffectiveness of training a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 6 publications
5
66
0
1
Order By: Relevance
“…The conceptualization of training in this way in the present study represents its main contribution. In general, the results obtained by the study were similar to the results of many other studies in the same context, which pointed out a significant as well as positive influence of training on organizational performance (Elnaga & Imran, 2013;Falola et al, 2014;Khan et al, 2011Khan et al, , 2017Kum et al, 2014;Percival et al, 2013;Saks & Burke-Smalley, 2014;Shaheen et al, 2013;Sherwani & Mohammed, 2015;Sultana et al, 2012;Talpur et al, 2016;Tangoukian et al, 2016;Umar et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The conceptualization of training in this way in the present study represents its main contribution. In general, the results obtained by the study were similar to the results of many other studies in the same context, which pointed out a significant as well as positive influence of training on organizational performance (Elnaga & Imran, 2013;Falola et al, 2014;Khan et al, 2011Khan et al, , 2017Kum et al, 2014;Percival et al, 2013;Saks & Burke-Smalley, 2014;Shaheen et al, 2013;Sherwani & Mohammed, 2015;Sultana et al, 2012;Talpur et al, 2016;Tangoukian et al, 2016;Umar et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The definitions provided in Sherwani and Mohammed's (2015) study confirmed that training, as a human resource management practice, is a good way to improve employees' knowledge, skills, and development opportunities. Citing Nel et al (2004), Kum et al (2014) argued that training results in a significant change in employees' behaviour, reduces defects and failures of projects, and increases the abilities of the employees to progress and perform more projects. Khan et al (2017) and Talpur et al (2016) added that employee training and development programmes lead to enhanced job performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…When it has been determined that out of all people working in organization which employees should be given training and which areas they need training only then the training can be launched properly (Kum & Cowden, 2014). People working in an organization create workforce, and the work force should be skilled enough to perform in well interest of company.…”
Section: Business Management and Strategymentioning
confidence: 99%
“…Traditional organizations hierarchy is that of Military style of downward looking as military is considered as the oldest and the largest organization as a group. And in response to that, Katcher and Snyder (2003) articulated development and the effect of training on employees can mostly encourage growth within the workers and the organization in conjunction with each other (Kum, Cowden, Karodia, 2014). Training and development helps in acquiring knowledge base and in application of developed knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%